On the Nature of the Core of α Centauri A: The Impact of the Metallicity Mixture - Nsamba, Benard; Campante, Tiago L.; Monteiro, Mário J. P. F. G.; Cunha, Margarida S.; Sousa, Sérgio G. (Frontiers in Astronomy and Space Sciences, 2019)
Forward asteroseismic modeling plays an important role toward a complete understanding of the physics taking place in deep stellar interiors. With a dynamical mass in the range over which models develop convective cores while in the main sequence, the solar-like oscillator α Centauri A presents itself as an interesting case study. We address the impact of varying the metallicity mixture on the determination of the energy transport process at work in the core of α Centauri A. We find that ≳ 70% of models reproducing the revised dynamical mass of α Centauri A have convective cores, regardless of the metallicity mixture adopted. This is consistent with the findings of Nsamba et al., where nuclear reaction rates were varied instead. Given these results, we propose that α Centauri A be adopted in the calibration of stellar model parameters when modeling solar-like stars with convective cores.